Risk of suicide in users of β-adrenoceptor blockers, calcium channel blockers and angiotensin converting enzyme inhibitors - Sørensen, Henrik Toft (Blackwell Science Inc, 2001)
AIMS: To examine the risk of suicide in users of β-adrenoceptor blockers, calcium channel blockers, and angiotensin converting enzyme inhibitors. METHODS: We conducted a cohort study based on linkage of a population-based prescription registry in North Jutland County, Denmark, and the nationwide Death Registry. From 1989 to 1995 there were 58 529 users of β-adrenoceptor blockers, calcium channel blockers, and angiotensin converting enzyme inhibitors. The mortality rates from suicides in the cohort members were compared with the rates in the general population. RESULTS: One hundred and four suicides occurred in the cohorts. The standardized mortality ratio for suicide in users of β-adrenoceptor blockers was 1.6 (95% confidence interval: 1.2–2.1), in users of calcium channel blockers 1.2 (95% confidence interval: 0.8–1.7), and in users of angiotensin converting enzyme inhibitors 1.2 (95% confidence interval: 0.7–1.8). In users of β-adrenoceptor blockers, the risk of suicide was increased during the first 12 months after the start of therapy, standardized mortality ratio 2.1 (95% confidence interval: 1.2–3.5). There was a trend in the standardized mortality ratio of suicide from 0.9 (95% confidence interval: 0.4–1.9) in users of β-adrenoceptor blockers with low lipid solubility, to 1.6 (0.8–2.8) and 2.7 (1.7–4.1) in users of β-adrenoceptor blockers with medium and high lipid solubility, respectively. CONCLUSIONS: Users of medium and high lipid soluble β-adrenoceptor blockers may have an increased risk of suicide. Users of calcium channel blockers and angiotensin converting enzyme inhibitors do not seem to have a significantly increased risk of suicide.